Sleep restriction in elite soccer players: effects on explosive power, wellbeing, and cognitive function - Abbott, W.; Brett, A.; Watson, A. W.; Brooker, H.; Clifford, T. (Research Quarterly for Exercise and Sport, 2022)
Purpose: To investigate the cognitive, physical, and perceptual effects of sleep restriction (SR) in soccer players following a night match.